1998
DOI: 10.1046/j.1365-2249.1998.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface activation markers of T lymphocytes: role in the detection of infection in neonates

Abstract: SUMMARYDiagnosis of perinatal infection in the newborn is difficult; there may be few clinical signs and current tests are slow or non-specific. Detection of organisms, antigen or specific antibody to common pathogens often requires repeat samples and does not give immediate results. Haematological parameters, although relied upon frequently to diagnose infection in the neonate prior to a positive bacterial isolation, are unreliable and insensitive. Indicators such as an increase in neutrophil band cell counts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 15 publications
4
34
0
Order By: Relevance
“…Other surface markers of diagnostic relevance include CD69 on NK cells and CD69, CD45RA, CD45RO and CD25 on peripheral T lymphocytes [36,44]. NK cell CD69 was a sensitive marker for diagnosing neonatal infection, correctly identifying 13 of 16 infants with septicemia [15,36].…”
Section: Expression Of Surface Markers On Nk and T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other surface markers of diagnostic relevance include CD69 on NK cells and CD69, CD45RA, CD45RO and CD25 on peripheral T lymphocytes [36,44]. NK cell CD69 was a sensitive marker for diagnosing neonatal infection, correctly identifying 13 of 16 infants with septicemia [15,36].…”
Section: Expression Of Surface Markers On Nk and T Cellsmentioning
confidence: 99%
“…NK cell CD69 was a sensitive marker for diagnosing neonatal infection, correctly identifying 13 of 16 infants with septicemia [15,36]. CD69 expression on NK cells together with CD45RA, CD45RO, CD25 and CD69 expression on T cells indicated that in infected infants, there were significant increases in at least two of the inflammatory mediators [36,44]. A recent study [34], including a large cohort of very low birthweight infants, was unable to confirm the usefulness of lymphocyte CD45RO and CD25 for diagnosing late-onset bacterial infection.…”
Section: Expression Of Surface Markers On Nk and T Cellsmentioning
confidence: 99%
“…For example, in all infants with proven bacterial infection, the proportion of CD45RO+ cells returned to a normal range within 6 weeks. In contrast, in cases of viral infection, a high percentage of CD45RO+ cells persisted for at least 12-20 weeks 19 . Also, changes in the proportion of CD45RO+ and/or CD45RA+ cells in peripheral blood of adults have been observed in several chronic conditions, such as psoriasis 24 , rheumatoid arthritis 25 , atopic asthma 26 , human immunodeficiency virus infection 27,28 and renal allograft rejection 20,21,23 .…”
Section: Surface Markersmentioning
confidence: 87%
“…An isotype control was employed for FITC and PE fluorescence. These gated cells were analyzed for CD45RA and CD45RO (dim and bright cells) 19 . The percentage of positive cells for the fluorescent antibody was recorded, and the results reported as a percentage of CD4+ lymphocytes.…”
Section: Flow Cytometry Studiesmentioning
confidence: 99%
See 1 more Smart Citation